KEBERADAAN PASAR NAGARI SISAWAH KABUPATEN SIJUNJUNG TAHUN 1998-2013 - Siska, Felia - (Pendidikan Sejarah, 2014)
Issues that were examined in this study is about Pasar Nagari Sisawah In Sijunjung Regency in 1998-2013. In 1998,, visitors in Pasar nagari Sisawah was very crowded, many merchans who came from outsideSisawah village traded to this market by using a four-wheel vehidcle, watercraft and also by walking. Since2000, this market it made as centre of communityâs economy, entertainment facilities, gathering public facilitiesbegan to empty by visitors. As for issues that concern in this study are first ; how the history pasar nagariSisawah in Sijunjung regency. Second ; how the development of pasar nagari Sisawah in 1998-2013. Third ;How societyâs view of Sisawah market in 1998-2013. Historical society is the using method. First, Heuristic orstages of collecting data to obtain a variety of relevan source utilize, after obtaining data, Internal and externalcritism conducted by testing of authenticity and validity of the data, is it relevant or not. And the fourthpresentation of research results in scientific writing and thesis. From the result of this study can be concludedthat the development of pasar nagari Sisawah is devided into two periods, in 1998-2005 and 2006-2013. In1998-2005, it has six permanent inns with crowded merchants and visitors, both from Sisawah village and otherregions, and management of the market was under âhe density of indegenous Villageâ (Kerapatan Adat Nagari)and then in zool it managed by village under the Department of industry and trade cooperative (DinasKopperindag) Sijunjung regency. In 2006-2013 period, pasar nagari Sisawah inns renovated in 2006, 2007,2009, and 2013, but there was a decrease of merchants and visitors. It caused by appearance of Ambek andSenggol bazaar in Sisawah Village. Society view about pasar nagari Sisawah was studied in two periods, in1998-2005 and 2006-2013. At first period, society view about pasar nagari Sisawah existence showed by needsof the community to the market was very high whereas at s at second period, pasar Sisawaht existence forpeople/society just as economic needs only or there was a change of societyâs view to the pasar nagari Sisawahexistence.